Efektivitas Penerapan Model Blended Learning Berbasis Google Classroom terhadap Hasil Belajar Siswa pada Pembelajaran Sejarah Kelas XI MIPA di SMA Negeri 4 Pandeglang - Dila Maulida Fadilah, Dila Maulida Fadilah; Mohammad Ali Fadillah, Mohammad Ali Fadillah; Tb. Umar Syarif Hadi Wibowo, Tb. Umar Syarif Hadi Wibowo (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the effectiveness of applying the Google Classroom-based blended learning model to student learning outcomes in history learning class XI Mipa at SMA Negeri 4 Pandeglang. Class XI MIPA at SMA Negeri 4 is the population taken for this study which consists of 5 classes. The research method used in this research is quasi-experimental. Sampling was done through nonprobability sampling technique. The sample in this study was class XI MIPA 4 as the experimental class and class XI MIPA 3 as the control class. The research was carried out on January 17 2023 – February 27 2023. The research results are as follows; The results showed that students' history learning outcomes in the experimental class were better than the control class. Testing the hypothesis through a two-party t-test using the polled variance formula obtained tcount = 3.82 > ttable 1.667 with α = 0.05. Thus, H0 is rejected and Ha is accepted. It can be concluded that the students' history learning outcomes by applying the Google Classroom-based belived learning model are better than the students' history learning outcomes by applying the discovery learning model in class XI MIPA at SMA Negeri 4 Pandeglang. The average posttest gain for the experimental class = 78.75 and for the control class = 71.78 shows that the experimental class has an average difference of 6.97.